Rak in vadba - But-Hadžić, Jasna (Šport (Ljubljana), 2016)
Cancer is one of the leading causes of mortality in Slovenia. The studies have shown the significant importance of regular physical exercise in the reduction the incidence of two of the most common forms of cancer, breast cancer and colon cancer. Regular physical activity lowers the risk of colorectal and breast cancer up to 25% and 12%, respectively. The exercise can be important during and after cancer therapy as it increases the quality oflife, reduces fatigue and in some forms of cancer improves overall survival.
Keywords: breast cancer; colon cancer; physical activity; rak debelega črevesa in danke; rak dojke; sport; šport; telesna dejavnost; vadba